Cells function as a ternary logic gate to decide migration direction under integrated chemical and fluidic cues. Issue 4 (16th December 2022) - Moon, Hye-ran; Saha, Soutick; Mugler, Andrew; Han, Bumsoo
Abstract : A reverse-engineered systems biology framework of directed cell migration in which cells function as a ternary logic gate to decode entangled chemical and fluidic cues to determine migration direction. Abstract : Cells sense various environmental cues and subsequently process intracellular signals to decide their migration direction in many physiological and pathological processes. Although several signaling molecules and networks have been identified in these directed migrations, it still remains ambiguous to predict the migration direction under multiple and integrated cues, specifically chemical and fluidic cues. Here, we investigated the cellular signal processing machinery by reverse-engineering directed cell migration under integrated chemical and fluidic cues. We imposed controlled chemical and fluidic cues to cells using a microfluidic platform and analyzed the extracellular coupling of the cues with respect to the cellular detection limit. Then, the cell's migratory behavior was reverse-engineered to build a cellular signal processing system as a logic gate, which is based on a "selection" gate. This framework is further discussed with a minimal intracellular signaling network of a shared pathway model. The proposed framework of the ternary logic gate suggests a systematic view to understand how cells decode multiple cues and make decisions about the migration direction.